T Takitia New member Joined Jul 11, 2007 Messages 18 Jul 24, 2007 #1 Please explain to me how they came up 4 in the following equation 3x -2y +8 -2y = -3x +8 y = 3/2 x-4 I need this step explianed before I can move forward.

Please explain to me how they came up 4 in the following equation 3x -2y +8 -2y = -3x +8 y = 3/2 x-4 I need this step explianed before I can move forward.

tkhunny Moderator Staff member Joined Apr 12, 2005 Messages 9,971 Jul 25, 2007 #2 -2/(-2) = 1 ==> y -3/(-2) = 3/2 ==> (3/2)x 8/(-2) = -4 ==> -4

S Subhotosh Khan Super Moderator Staff member Joined Jun 18, 2007 Messages 18,354 Jul 25, 2007 #3 Takitia said: Please explain to me how they came up 4 in the following equation 3x -2y +8 -2y = -3x +8...........divide by (-2) both sides y = 3/2 x-4 I need this step explianed before I can move forward. Click to expand...

Takitia said: Please explain to me how they came up 4 in the following equation 3x -2y +8 -2y = -3x +8...........divide by (-2) both sides y = 3/2 x-4 I need this step explianed before I can move forward. Click to expand...